A Low-Cost Fluorescent Sensor for pCO2 Measurements - Xudong Ge; Yordan Kostov; Robert Henderson; Nicholas Selock; Govind Rao (Chemosensors, 2014)
Global warming is believed to be caused by increasing amounts of greenhouse gases (mostly CO2) discharged into the environment by human activity. In addition to an increase in environmental temperature, an increased CO2 level has also led to ocean acidification. Ocean acidification and rising temperatures have disrupted the water’s ecological balance, killing off some plant and animal species, while encouraging the overgrowth of others. To minimize the effect of global warming on local ecosystem, there is a strong need to implement ocean observing systems to monitor the effects of anthropogenic CO2 and the impacts thereof on ocean biological productivity. Here, we describe the development of a low-cost fluorescent sensor for pCO2 measurements. The detector was exclusively assembled with low-cost optics and electronics, so that it would be affordable enough to be deployed in great numbers. The system has several novel features, such as an ideal 90° separation between excitation and emission, a beam combiner, a reference photodetector, etc. Initial tests showed that the system was stable and could achieve a high resolution despite the low cost.